Water Quality Monitoring of Pesticides and Associated Health Impacts - Thacker, N.P.; Bassin, J.K.; Nitnaware, V.; Biswas, M.; Das, S.K.; Vaidya, P. (Asian Journal of Chemistry, 2010)
In the present work we report the monitoring of water quality in the perspective of pesticides and their impact on human health.